Effect of Task Load Interventions on Fatigue in Emergency Medical Services Personnel and Other Shift Workers: A Systematic Review. (15th February 2018) - Studnek, Jonathan R.; Infinger, Allison E.; Renn, Megan L.; Weiss, Patricia M.; Condle, Joseph P.; Flickinger, Katharyn L.; Kroemer, Andrew J.; Curtis, Brett R.; Xun, Xiaoshuang; Divecha, Ayushi A.; Coppler, Patrick J.; Bizhanova, Zhadyra; et al.
Abstract: Background : Modifying the task load of Emergency Medical Services (EMS) personnel may mitigate fatigue, sleep quality and fatigue related risks. A review of the literature addressing task load interventions may benefit EMS administrators as they craft policies related to mitigating fatigue. We conducted a systematic review of the peer-reviewed literature to address the following question: "In EMS personnel, do task load interventions mitigate fatigue, mitigate fatigue-related risks, and/or improve sleep?" (PROSPERO 2016:CRD42016040114).Methods : We performed a systematic review of the literature that described use of randomized controlled trials, quasi-experimental studies, and observational study designs. We retained and reviewed research that involved EMS personnel or similar shift worker groups 18 years of age and older. Studies of 'healthy volunteers' and non-shift worker populations were excluded. Studies were included where the methodology of the study implied a theoretical framework of task load (or workload) affecting fatigue, and then fatigue related outcomes. Outcomes of interest included personnel safety, patient safety, personnel performance, acute fatigue, and cost to system. We used the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) methodology to summarize findings and assess quality of evidence from very low to high quality.Results : The search strategy yielded 3, 394 unique records resulting in 58 records included as potentially eligible. An additional 69 studies were reviewed in full following searches of bibliographies. We detected wide variation in the description and measurement of task load in the retained and excluded research. Among 127 potentially relevant studies reviewed in full, five were judged eligible. None of the retained studies reported findings germane to personnel safety, patient safety, or cost to system. We judged most studies to have serious or very serious risk of bias.Conclusions : The effect of task load interventions on fatigue, fatigue-related risks, and/or sleep quality was not estimable and the overall quality of evidence was judged low or very low. There was considerable heterogeneity in how task load was defined and measured.